Hubungan Depresi Dengan Kelelahan Pada Pasien Yang Menjalani Hemodialisa - Syafira, Deby Ayu; Prihati, Dyah Restuning; Aini, Dwi Nur (Citra Delima Scientific journal of Citra Internasional Institute, 2024)
The body's digestive products are distributed and excreted by the kidneys. Reduced kidney function will disrupt the body's balance, causing a buildup of waste products, especially urea (which causes uremia), fluid balance disorders, and excess fluid and electrolytes. Patients undergoing hemodialysis therapy can experience psychological and physical side effects. The aim of the study was to determine the relationship between depression and fatigue in patients undergoing hemodialysis. In this cross-sectional study, 43 participants were randomly selected. The questionnaire to measure the level of fatigue uses the Fatigue Severity Scale (FSS) and Beck Depression Inventory (BDI) to assess depressive symptoms. This research uses a non-parametric test with Spearman Rank. The results of the study explained that 14 respondents who underwent hemodialysis experienced mild depression and fatigue. From these results, a significance value of 0.005 was obtained and a sperm correlation value of 0.422. In conclusion, the data shows a positive correlation of moderate strength between the level of fatigue and depression experienced by hemodialysis patients. This shows that the more tired patients undergoing hemodialysis are, the more likely they are to experience depression. The results of this study are used as evidence-based in conducting interventions in treating patients with chronic kidney failure who experience fatigue and depression while undergoing hemodialysis.